"It kinda breaks my heart": LGBTQ young adults' responses to family rejection. Issue 3 (11th January 2022) - DeChants, Jonah P.; Shelton, Jama; Anyon, Yolanda (Yoli); Bender, Kimberly
Abstract: Objective: This study examines the realities of LGBTQ young adults experiencing family rejection, specifically illuminating forms of heterosexist and cisgenderist family rejection and their impact on LGBTQ young adults. Background: Extant research indicates family rejection is a driving factor in the overrepresentation of LGBTQ young adults among young adults experiencing homelessness. Method: This study analyzed two waves of interviews with 15 LGBTQ young adults. It addressed two research questions: (a) What kinds of heterosexist and cisgenderist rejection do LGBTQ young adults experience from their parents or guardians? and (b) How do LGBTQ young adults react to and experience that rejection? Results: Participants reported multiple forms of heterosexist and cisgenderist rejection from their families, including increased heterosexism and cisgenderism in the home after coming out, increased arguments and conflict after coming out, abuse and neglect, silence and avoidance, control and isolation, and revoking young people's access to housing. Participants' responses to these forms of rejection included pain, disconnection from their families, feeling stifled in the home, and the desire to resist. Conclusion: These findings illuminate specific forms and manifestations of heterosexist and cisgenderist family rejection and their impact on LGBTQ young adults. Implications: Implications for research include further exploration of how family rejection manifests in the families of LGBTQ young adults. Implications for clinical practice include developing tailored outreach and services for young adults experiencing family rejection and housing instability.